2021
DOI: 10.1016/j.trsl.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell functionality and hepatic insulin resistance are major contributors to type 2 diabetes remission and starting pharmacological therapy: from CORDIOPREV randomized controlled trial

Abstract: cell functionality and hepatic insulin resistance are major contributors to type 2 diabetes remission and starting pharmacological therapy: from CORDIOPREV randomized controlled trial.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Although previous studies have suggested that impairment in β-cell function predisposes the risk-allele carriers of the TCF7L2 variants to the progression of T2DM [ 8 , 9 ], the dysfunction in β-cell may be due to the insulin resistance that is more pronounced in healthy T-allele risk carriers [ 10 , 11 ]. There is evidence that participants with a family history of diabetes and genetic background of T2DM responded differentially to dietary and pharmacological treatment [ 65 , 66 ]. Regarding the metformin treatment, in participants with a new diagnosis of T2DM, insulin resistance decreased more among T-allele carriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have suggested that impairment in β-cell function predisposes the risk-allele carriers of the TCF7L2 variants to the progression of T2DM [ 8 , 9 ], the dysfunction in β-cell may be due to the insulin resistance that is more pronounced in healthy T-allele risk carriers [ 10 , 11 ]. There is evidence that participants with a family history of diabetes and genetic background of T2DM responded differentially to dietary and pharmacological treatment [ 65 , 66 ]. Regarding the metformin treatment, in participants with a new diagnosis of T2DM, insulin resistance decreased more among T-allele carriers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this response became less efficacious among participants with the progression of the disease [ 65 ]. In addition, the dietary intervention had little effect on the prevention and delay in initiating glucose-lowering treatment in subjects with a family history of T2DM and those with high hepatic insulin resistance and β-cell dysfunction [ 66 ]. Moreover, in observational studies, the effect of fatty acids (both diet and plasma) on the relationship between TCF7L2 and glycemic parameters has been more studied [ 51 , 53 , 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 was subsequently divided into two sections. [18][19][20][21][22][23][24] Section 1A lists the 4 trials with newly diagnosed T2D and no caloric restriction. Section 1B lists the 3 trials with newly diagnosed T2D and mild caloric restriction.…”
Section: Article Identification and Data Extractionmentioning
confidence: 99%
“…No trials were conducted in an African country. In fact, enrolment of people of African descent was described only in the two studies conducted in Barbados (24,27). These studies were small with 10 and 25 participants, respectively.…”
Section: Participant Characteristics: Country Race/ethnicity and Gendermentioning
confidence: 99%